Left inferior-parietal lobe activity in perspective tasks: identity statements - Arora, Aditi; Weiss, Benjamin; Schurz, Matthias; Aichhorn, Markus; Wieshofer, Rebecca C.; Perner, Josef (Frontiers in Human Neuroscience, 2015)
We investigate the theory that the left inferior parietal lobe (IPL) is closely associated with tracking potential differences of perspective. Developmental studies find that perspective tasks are mastered at around four years of age. Our first study, meta-analyses of brain imaging studies shows that perspective tasks specifically activate a region in the left IPL and precuneus. These tasks include processing of false belief, visual perspective, and episodic memory. We test the location specificity theory in our second study with an unusual and novel kind of perspective task: identity statements. According to Frege’s classical logical analysis, identity statements require appreciation of modes of presentation (perspectives). We show that identity statements, e.g., “the tour guide is also the driver” activate the left IPL in contrast to a control statements, “the tour guide has an apprentice.” This activation overlaps with the activations found in the meta-analysis. This finding is confirmed in a third study with different types of statements and different comparisons. All studies support the theory that the left IPL has as one of its overarching functions the tracking of perspective differences. We discuss how this function relates to the bottom-up attention function proposed for the bilateral IPL.